2006
DOI: 10.1021/es0525152
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fenton Reagent Dose on Coexisting Chemical and Microbial Oxidation in Soil

Abstract: The ability of modified Fenton reactions to promote simultaneous chemical and biological oxidation in an artificially contaminated soil was studied in batch laboratory slurry reactors. Tetrachloroethene (PCE) and oxalate (OA) were used to distinguish chemical oxidation from aerobic heterotrophic metabolism. PCE was mineralized by Fenton reactions, but OA was not oxidized. Indigenous soil microorganisms did not degrade added PCE aerobically but readily assimilated OA. Fenton reactions were promoted at the natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(25 citation statements)
references
References 23 publications
(36 reference statements)
2
23
0
Order By: Relevance
“…The final Cl − concentration was approximately 11 mM, resulting in a ratio of 3.7 mmol Cl − released/mmol PCE oxidized. This is similar to molar ratios observed by Ndjou'ou et al [26] for MF oxidation of PCE in soils using liquid H 2 O 2 . The amount of PCE oxidized (5.83 mmol, or 97%) was obtained by subtracting the mmol volatilized from the total mmol removed.…”
Section: Measuring O 2 Released From Cao 2 and H 2 Osupporting
confidence: 91%
See 2 more Smart Citations
“…The final Cl − concentration was approximately 11 mM, resulting in a ratio of 3.7 mmol Cl − released/mmol PCE oxidized. This is similar to molar ratios observed by Ndjou'ou et al [26] for MF oxidation of PCE in soils using liquid H 2 O 2 . The amount of PCE oxidized (5.83 mmol, or 97%) was obtained by subtracting the mmol volatilized from the total mmol removed.…”
Section: Measuring O 2 Released From Cao 2 and H 2 Osupporting
confidence: 91%
“…The dose of PCE in all three reactors was 6 mmol (3 mM, or 500 mg/L), and the dose of 2-propanol was 30 mM. Using 2-propanol was based on its effectiveness as a scavenger of • OH [26,28,29]. Analyses done at the end of the experiments (60 h) verified that no CaO 2 and no measurable amount of unreacted H 2 O 2 remained in the MF reactors.…”
Section: Measuring O 2 Released From Cao 2 and H 2 Omentioning
confidence: 95%
See 1 more Smart Citation
“…The oxidative stress, increase or decrease in pH (persulfate and Fenton's reagent, respectively), and change in redox conditions caused by ISCO treatments significantly alter subsurface conditions and are toxic to microbial populations (Buyuksonmez et al 1998;Macbeth et al 2007;Miller et al 1996). However, recent work indicates that, although chemical oxidation can temporarily reduce microbial activity, bacterial populations do regenerate contaminant degradation ability both in the field (Jones et al 2009;Koch et al 2007;Ladaa et al 2008;Luhrs et al 2006;Macbeth et al 2005;Studer et al 2009) and in laboratory experiments (Aunola et al 2006;Hood et al 2006;Kao and Wu 2000;Kulik et al 2006;Ndjou'ou et al 2006). In many cases, it has been concluded that ISCO pretreatment appears to improve overall remediation by (1) decreasing the concentration of pollutants to levels less toxic for the soil biota (Chapelle et al 2005), (2) improving bioavailability of the parent compound (Kulik et al 2006;Miller et al 1996), (3) producing bioavailable and biodegradable oxidized daughter compounds (Lee and Hosomi 2001;Marley et al 2003;Miller et al 1996;Nam et al 2001), or (4) providing oxygen for aerobic biological transformation of contaminants (Kulik et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Due to strong oxidizing ability, the advanced oxidation processes (such as ultrasonic oxidation [1][2][3], photocatalytic oxidation [4][5][6][7], and Fenton oxidation [8,9]) are increasingly used for analysis and degradation removal of organic pollutants in concerns of environmental analysis and protection. Among these processes, the photocatalytic oxidation seems to be the most attractive.…”
Section: Introductionmentioning
confidence: 99%